Analysis of Segmentation, Targeting, and Positioning of Indonesian Car Market in Determining The Proper Market for Wuling Motors - Suyanto, AMA; Prakoso, Wisnu Dega Wahyu (Advances in Social Sciences Research Journal, 2020)
In order to conform the market every single car in Indonesia are conducting a market strategy. One of those strategies is by applying a proper segmentation, targeting, and positioning. In 2019, Wuling Motors has the highest market growth compared to other car brands in Indonesia. Although Wuling Motors’s market growths are high, in 2019 Wuling Motors’s market share are below the top 5 car brands in Indonesia. The purposes of this research are: 1) to discover the conformity of Wuling Motors segmentation towards the Indonesian market; 2) to discover the conformity of Wuling Motors market target towards the Indonesian market; 3) to discover the position result of Wuling Motors towards the Indonesian market. Respondent for this research uses 400 respondents. This research classified as mix method research with descriptive analysis. Method used for this research are cluster analysis (K-means cluster) based on the demographic, geographic, psychographic, behavioral that supporting the market preference. Geographic segmentation is classified using crosstab tabulation analysis. In analyzing the positioning, multidimensional scaling used as the method with 2 dimensions perceptual mapping. To re-confirming the data about Wuling Motors’s segmentation, targeting and positioning, author conducted an interview to Wuling Motors’s marketing division located in Bandung, Indonesia. The result of this research are formed 4 various cluster based on respondents age and monthly income, which, every cluster has its own characteristics in selecting a cars, and gathered most dominant respondents domicile based on the crosstab analysis. In MDS, gathered 4 quadrants with similarity between model and safety for respondents with age are above the average, and income also above the average. The final result is, Wuling Motors has implementing a conform segmentation, targeting and positioning towards the Indonesian market.